Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Yrribarren Salcedo, Lisbeth Brenda (2018)
The purpose of this professional proficiency work is to structure a business analysis and strategic plan for the Japanese Fast Retailing Group, owner of UNIQLO, GU, Theory, Comptoir des Contonniers, Princesse tam.tam and J Brand; with the purpose of assessing their entry to Peru in 2019. The analysis will begin with the internal diagnosis in order to establish their capabilities, resources and key areas of the company. Then an external diagnosis will be made aimed at the Peruvian market to determine the opportunities and threats of the environment. The formulation of the strategy will focus on analyzing UNIQLO, the most representative brand of the group that contributes more than 80% of its income, since this would be the one chosen to enter the country. Finally, changes to its best implementation and a control panel with management indicators will be proposed to ensure monitoring. It is important to mention that this plan will have greater emphasis in the area of ¿¿Marketing and Logistics, which were selected for the degree process.